PEMAHAMAN KONSEP KUNCI GEOGRAFI PADA MATERI POSISI STRATEGIS INDONESIA UNTUK MENINGKATKAN LITERASI GEOGRAFIS SISWA SMA NEGERI 1 LOLOFITU MOI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students' learning activities in understanding key concepts of geography in the material of Indonesia's Strategic Position and to analyze the increase in geographic literacy after the implementation of learning based on key concepts of geography in class XI Phase F of SMA Negeri 1 Lolofitu Moi. The method used is quantitative with a quasi-experimental design. The research sample consisted of class XI-1 F as the experimental class (33 students) and class XI-4 F as the control class (32 students) selected using a purposive sampling technique. Learning activity data was obtained through observation sheets, while geographic literacy was measured through pre-test and post-test, then analyzed using normality test, homogeneity test, t-test, and N-Gain results. The results showed that student learning activities in the experimental class increased from 36% to 78%, while in the control class from 17% to 48%. The average post-test score of the experimental class was 84, higher than the control class at 64.4. The results of the t-test showed a significance value of 0.000 <0.05, so there was a difference in learning based on key concepts of geography on students' geographic literacy. The N-Gain results showed an increase of 66.56% in the experimental class (medium category) and 29.75% in the control class (low category). Thus, learning based on key geography concepts has proven effective in improving students' learning activities and geographic literacy.